The Use of Short Clip Movie on Reading Comprehension at Higher Education - Putri, Azzahra Namira; Rachman, Dzul (Borneo Educational Journal (Borju), 2024)
Reading is a fundamental skill that requires deliberate study and mastery in order to acquire knowledge and collect information. Conversely, videos provide an enjoyable method for both language acquisition and entertainment. The goal of this study is to investigate if watching short clip movies can enhance the reading comprehension of higher education students, who often have challenges in learning to read. The research approach employed in this study is correlation. The researcher collects data from second semester students at the English Language Education Study Program, Teacher Training and Education Faculty Universitas Muhammadiyah Kalimantan Timur. The study used a convenience sample approach to gather data. The allocation of this research is done in a convenience sampling among students belonging to a specific class. The researcher will employ a questionnaire and a test to gather data regarding the experience of watching a brief movie clip with English subtitles. The test will specifically focus on measuring reading comprehension abilities. The study findings indicate a very low correlation and a positive correlation between students' reading comprehension and using of short clip movie.